Nonlinear polariton parametric emission in an atomically thin semiconductor based microcavity - Zhao, Jiaxin (2022)
Parametric nonlinear optical processes are at the heart of nonlinear optics underpinning the central role in the generation of entangled photons as well as the realization of coherent optical sources. Exciton-polaritons are capable to sustain parametric scattering at extremely low threshold, offering a readily accessible platform to study bosonic fluids. Recently, two-dimensional transition-metal dichalcogenides (TMDs) have attracted great attention in strong light–matter interactions due to robust excitonic transitions and unique spin-valley degrees of freedom. However, further progress is hindered by the lack of realizations of strong nonlinear effects in TMD polaritons. Here, we demonstrate a realization of nonlinear optical parametric polaritons in a WS2 monolayer microcavity pumped at the inflection point and triggered in the ground state. We observed the formation of a phase-matched idler state and nonlinear amplification that preserves the valley population and survives up to room temperature. Our results open a new door towards the realization of the future for all-optical valley polariton nonlinear devices.